Comparing Performance of Group Communications Protocols Over SCB versus Routed MANET Networks - Suri, Niranjan; Bredy, Maggie; Campioni, Lorenzo; Nilsson, Jan; Cramer, Eelco; Fronteddu, Roberto; Tortonesi, Mauro (MILCOM IEEE Military Communications Conference, 2022)
Scalable Cooperative Broadcast (SCB) is a relatively new technology for wireless radios that is particularly well-suited to broadcast and multicast communications. In this paper, we evaluate the performance of Group Communications protocols over SCB versus over a more traditional MANET network using OLSRv2 for routing. The evaluation is based on the Anglova military scenario and measures the overall delivery ratio and delivery latency for blue force messages as well as the overall bandwidth utilized by both the middleware and any network services (OLSRv2 for routing and SMF for forwarding). Our results show that SCB is more efficient in terms of delivering data such as blue force messages, which are intended to be received by multiple (or all) recipients.